(untitled) (Análisis Económico, 2024)
The subject of Stochastic Processes is highly specialized and here only we present an assessment of the subject. To explain uncertainty dynamics a model is required which consists of a system et stochastic differential equation. We provide a critical synthesis of the literature and analyze the geometric behavior of a basket of useful models, stopping at computer simulation and borrowing ideas taken from the Monte Carlo method.